Morphological Characteristics of Cucumber (Cucumis sativus L.) Leaves under Different Environmental Conditions - Putri, Ulfa Dwi; Vauzia, Vauzia; Chatri, Moralita; Handayani, Dezi (Jurnal Biologi Tropis, 2025)
Cucumber (Cucumus sativus L.) is a horticultural crop with high water content, low calories, and potential benefits as an antibiotic, lipid-lowering agent, and antioxidant. This Plant has great potential for cultivation, as it can be marketed both domestically and internationally. However, cucumber production remains relatively low and has declined from 2022 to 2023. This decrease is caused by several factors, one of which is changing environmental conditions. Therefore, the plant's ability to adapt to different environmental conditions becomes a crucial factor in the effort to develop cucumber cultivation. Based on this, the present study was conducted to investigate the morphological characteristics of cucumber leaves under different environmental conditions. This research was conducted from September 2024 to January 2025 in two different locations, namely Kota Padang and Kamang Magek. The method used in this study was a Completely Randomized Design (CRD) with 2 treatments and 20 replications. The data obtained were analyzed using a t-test at a 5% significance level. The results showed that there were significant differences in leaf length and the number of leaf vein branches between the two research locations. The average leaf length in Kota Padang was higher, at 12.21 cm, compared to Kamang Magek, which only reached 10.42 cm. In contrast, the average number of leaf vein branches in Kamang Magek was higher, at 14.65, compared to Kota Padang, which was only 13.3. Meanwhile, no significant differences were found in leaf width and petiole length between the two locations.